The Emergence of Organizations and Markets 2012
DOI: 10.23943/princeton/9780691148670.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Institutional Genesis

Abstract: This chapter examines eleven regions in the United States in the 1980s and 1990s that were all rich in resources—ideas, money, and skills—which might have led to the formation of life sciences clusters. Yet only three of the regions—the San Francisco Bay Area, Boston, and San Diego—developed into robust industrial districts for biotechnology. Most research on the emergence of high-tech cluster samples on successful cases and traces backward to find a developmental pattern. In contrast, rather than read in reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 0 publications
2
26
0
3
Order By: Relevance
“…Overlooking the coexistence of two competing frames about cooperation and the implications on agents' behavior was one of the reasons that limited institutions' ability to govern the network. Nevertheless, our results confirm that institutions, as reported in studies on network governance describing goal-directed networks (see, among others, Powell et al, 2012), can play a significant role in affecting network dynamics.…”
Section: Towards a Dynamic Theory Of Network Failure: The Emerging Frameworksupporting
confidence: 90%
See 1 more Smart Citation
“…Overlooking the coexistence of two competing frames about cooperation and the implications on agents' behavior was one of the reasons that limited institutions' ability to govern the network. Nevertheless, our results confirm that institutions, as reported in studies on network governance describing goal-directed networks (see, among others, Powell et al, 2012), can play a significant role in affecting network dynamics.…”
Section: Towards a Dynamic Theory Of Network Failure: The Emerging Frameworksupporting
confidence: 90%
“…Network structural and operational dynamics can follow different trajectories, driven by two main (ideal-type) processes: goal-directedness and serendipity (Kilduff & Tsai, 2003). Goaldirected networks develop around a specific goal, and are characterized by the emergence of a coordinating entity -a broker (Lingo & O'Mahony, 2010), a network-orchestrator (Dhanarai & Parkhe, 2006;Paquin & Howard-Grenville, 2013), a catalyst (Furnari, 2014), or an anchor-tenant (Powell, Packalen, & Whittington, 2012) -which helps "to build the network, coordinate and manage its activities, support network firms and network-level goals, and provide a centralized location for performing key activities of the network" (Human & Provan, 2000, p. 330). When networks emerge from serendipity, individual agents may decide whom to connect with, what to transact, and so on, "without guidance from any central network agent concerning goals or strategy" (Kilduff & Tsai, 2003, p. 90).…”
Section: Defining Network Failurementioning
confidence: 99%
“…Many observers have noted the role that Stanford University, and also UC Berkeley, played in Silicon Valley's ascent to become the global center of the computer industry and related high-tech activities (e. g., Kenney and Mowery 2014;Klepper 2016). As documented by Powell et al (2012), university research and academic entrepreneurship were perhaps even more decisive in the emergence and evolution of U.S. biotechnology clusters, and similar observations have been made elsewhere. Moving from individual cases to a more aggregate econometric approach, the impact of university research on regional innovation was shown in numerous empirical contexts including, e. g., the U.S. (Jaffe 1989;Acs et al 1992), Germany (Fritsch and Slavtchev 2007;Schubert and Kroll 2014), or Italy (Cowan and Zinovyeva 2013).…”
supporting
confidence: 62%
“…Employees from the failed diagnostics company Hybritech stayed in the San Diego area and went on to found start-ups that routinely exchanged information and collaborated with each other-in large part because of having previously worked together at Hybritech. 219 How should this second role of employee migration-enhancing the local reservoir of trust across firms in innovation clusters-inform courts' treatment of the inevitable disclosure doctrine and the enforceability of covenants not to compete? In essence, appreciating the importance of migration for trust-building uncovers an additional benefit to the free circulation of human capital.…”
Section: Duty Of Loyalty and Duty Of Confidencementioning
confidence: 99%